Efficacy and Safety of Conventional Halstead versus Modified Infra Alveolar Block Technique for Third Molar Extraction - Azmat, Saadat Ullah; Muhammad Junaid; Ashfaq Ahmed; Syed Junaid Hussain Bukhari; Ashar Waheed; Faisal Asif (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare efficacy of block, safety profile and frequency of adverse effects after using conventional Halstead technique versus experimental modified Halstead technique for inferior nerve block in patients planned for third molar extraction Study Design: Quasi-experimental study Place and Duration of Study: Orthodontics department of Armed Forced Institute of Dentistry (AFID), Rawalpindi, Pakistan, from Jun 2024 to Jul 2025 Methodology: Participants were placed in Group-A (n=160) to receive conventional Halstead approach for the block and Group B (n=160) to receive modified infra alveolar block technique for a modified Halstead approach. Primary variables studied were frequency of re-anesthesia required due to persistent pain after starting the procedure, electric discharge sensation felt, local complications including swelling and bleed, mean onset of block time at the level of tongue and lower lip. Secondary variables studied were pain during injection and extraction. Results: Median pains scores on the VAS during injection were 2.00 (2.00) versus 3.00 (2.00) (p<0.001) and median pain scores during extraction were 3.00 (2.00) versus 5.00 (3.00) (p<0.001). Re-anesthesia requirement was seen in 46(28.7%) patients in Group-A versus 72(45.0%) patients in Group-B (p=0.003). Complete block failure was reported in 05(3.1%) patients in Group-A versus 08(5.0%) patients in Group-B (p=0.396). Conclusion: Conventional Halstead approach still offers the better patient outcomes with respect of onset of block time, frequency of local complications, median pain scores during the procedure, requirement of re-anesthesia and overall block failure.